The European Health Data Space fails to bridge digital divides. (8th July 2022) - van Kessel, Robin; Wong, Brian Li Han; Forman, Rebecca; Gabrani, Jonila; Mossialos, Elias
Abstract : Closer engagement with patients and the public is essential